On 2-Absorbing Quasi Primary Submodules - Koc, Suat; Uregen, Rabia Nagehan; Tekir, Unsal (UNIV NIS, FAC SCI MATH, 2017)
Let R be a commutative ring with nonzero identity, and let M be a nonzero unital R-module. In this article, we introduce the concept of 2-absorbing quasi primary submodules which is a generalization of prime submodules. We define 2-absorbing quasi primary submodule as a proper submodule N of M having the property that abm is an element of N, then ab is an element of root(N :(R) M) or am is an element of rad(M)(N) or bm is an element of rad(M)(N) : Various results and examples concerning 2-absorbing quasi primary submodules are given.
Keywords: multiplication module; prime submodule; 2-absorbing submodule; RADICALS; Mathematics